THE EFFECT OF WORKING CAPITAL TURNOVER, TURNOVERCASH, RECEIVABLES TURNOVER ON PROFITABILITY WITH DIVIDEND POLICY AS A MODERATION VARIABLE IN CHEMICAL SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2020-2023 PERIOD - Muhammad Tabrani; Dedi Alfian; Yudi Febriansyah; Donny Firmansyah; Lili Hendrayani; Indrayani; Muammar Khaddafi (RADJA PUBLIKA, 2023)
Each company is established for an unlimited period of time or according to the company's ability to maintain the viability of its activities. To realize this, the company must optimize the achievement of profits or profits in order to maintain the company's activities, both short and long term. Profit is an indicator of a company's performance, continuously increasing profit growth can give a positive signal to a company. With profits that grow positively, it is hoped that it will be able to increase the company's profits. The purpose of this research was to analyze the effect of working capital turnover, cash turnover, accounts receivable turnover to profitability dividend policy as moderation variables in chemical sub-sector companies listed on the Indonesia Stock Exchange for the period 2020-2023. The sample used in this research was the entire population of 11 companies. In this research, the sampling technique used is non-probability sampling with the technique taken is saturated sampling (census). The research method uses the associative method with a quantitative approach with analysis of Partial Least Square (PLS) analysis techniques with the SmartPLS Version 4.0 program. The results of this research state that the working capital turnover variable has a positive and significant effect on profitability. Cash Turnover variable has a positive and significant impact on Profitability. Receivable Turnover variable has a positive and significant effect on Profitability. The dividend policy variable has a positive and significant effect on profitability.